Molecular Biology in Marine Science: Scientific Questions, Technological Approaches, and Practical Implications (The National Academies Press, 1994)
Keywords: Biology and Life Sciences; Earth Sciences

Oil in the Sea IV: Quick Guide for Practitioners and Researchers - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
This booklet provides key insights from Oil in the Sea IV: Inputs, Fates, and Effects, published in 2022, which benefited from significant advancements in scientific methods to detect the input and fates of oil in the sea, and from lessons learned from the Deepwater Horizon explosion and oil spill in 2010. Going beyond previous reports, Oil in the Sea IV includes analysis of human health impacts of oil in the sea, oil in the Arctic marine environment, and prevention and response efforts that can help to both reduce the amount of oil reaching the sea and minimize its effects. The booklet is meant to serve as a reference guide to all those involved in oil spill research and response.
Keywords: Environment and Environmental Studies; Earth Sciences

50 Years of Ocean Discovery: National Science Foundation 1950-2000 - National Research Council (The National Academies Press, 2000)
This book describes the development of ocean sciences over the past 50 years, highlighting the contributions of the National Science Foundation (NSF) to the field's progress. Many of the individuals who participated in the exciting discoveries in biological oceanography, chemical oceanography, physical oceanography, and marine geology and geophysics describe in the book how the discoveries were made possible by combinations of insightful individuals, new technology, and in some cases, serendipity. In addition to describing the advance of ocean science, the book examines the institutional structures and technology that made the advances possible and presents visions of the field's future. This book is the first-ever documentation of the history of NSF's Division of Ocean Sciences, how the structure of the division evolved to its present form, and the individuals who have been responsible for ocean sciences at NSF as "rotators" and career staff over the past 50 years.
Keywords: Earth Sciences; Environment and Environmental Studies

The Community Development Quota Program in Alaska - National Research Council (The National Academies Press, 1999)
This book reviews the performance and effectiveness of the Community Development Quotas (CDQ) programs that were formed as a result of the Sustainable Fisheries Act of 1996. The CDQ program is a method of allocating access to fisheries to eligible communities with the intent of promoting local social and economic conditions through participation in fishing-related activities. The book looks at those Alaskan fisheries that have experience with CDQs, such as halibut, pollock, sablefish, and crab, and comments on the extent to which the programs have met their objectives—helping communities develop ongoing commercial fishing and processing activities, creating employment opportunities, and providing capital for investment in fishing, processing, and support projects such as infrastructure. It also considers how CDQ-type programs might apply in the Western Pacific.
Keywords: Agriculture; Earth Sciences

Science for Decisionmaking: Coastal and Marine Geology at the U.S. Geological Survey - National Research Council (The National Academies Press, 1999)
The coastlines of the United States are beautiful places to live, work and play. But, they are also very fragile areas whose ecosystems are vulnerable to mismanagement. There are many complex issues facing the ocean science community at the federal, state and local levels—this report reflects the conclusions and recommendations of the National Academies drawing on discussions with USGS as well as input from potential users, clients and collaborators of the Coastal and Marine Geology Program.
Keywords: Earth Sciences

Challenges in Ocean Policy (The National Academies Press, 2001)
Challenges in Ocean Policy summarizes the main messages of recent reports from the Ocean Studies Board, calling attention to two significant ocean issues — nutrient pollution and sustainable fisheries — that are likely to require high-level attention and policy decisions during the coming four years.
Keywords: Earth Sciences

Building Ocean Science Partnerships: The United States and Mexico Working Together - National Research Council (The National Academies Press, 1999)
Building Ocean Science Partnerships describes a set of potential ocean science projects for cooperative research between scientists from the United States and Mexico, particularly focused on the Pacific Coast of California and Baja California, the Gulf of California, and the Gulf of Mexico. Barriers to cooperation between scientists of the two nations are identified, and methods to overcome such barriers are recommended. The book describes how interactions can be promoted by enhancing opportunities for education and training, building and sharing scientific infrastructure, participating together in large-scale marine research programs and regional ocean observing systems, planning joint science events and publications, and developing sources of binational funding. Building Ocean Science Partnerships will be published in English and Spanish to make its contents widely accessible in the United States and Mexico.
Keywords: Earth Sciences

Opportunities in Ocean Sciences: Challenges on the Horizon (The National Academies Press, 1998)
Keywords: Earth Sciences

Review of Northeast Fishery Stock Assessments - National Research Council (The National Academies Press, 1998)
The collapse of cod, flounder, and haddock fish stocks in the Northeast United States has caused widespread concern among managers and fishers in the United States and Canada. The diminishing stocks have forced managers to take strict regulatory measures. Numerous questions have been raised about the adequacy of stock assessment science used to evaluate the status of these stocks and the appropriateness of the management measures taken. Based on these concerns, Congress mandated that a scientific review of the methodology and data used to evaluate these stocks be conducted. In this volume, the committee concludes that although there are improvements to be made in data collection, modeling uncertainty, and communicating between fishers, managers, and scientists, the scientific methods used in the Northeast stock assessments are sound. Recommendations are made on how the stock assessment process can be improved.
Keywords: Agriculture; Earth Sciences

Improving Fish Stock Assessments - National Research Council (The National Academies Press, 1998)
Ocean harvests have plateaued worldwide and many important commercial stocks have been depleted. This has caused great concern among scientists, fishery managers, the fishing community, and the public. This book evaluates the major models used for estimating the size and structure of marine fish populations (stock assessments) and changes in populations over time. It demonstrates how problems that may occur in fisheries data—for example underreporting or changes in the likelihood that fish can be caught with a given type of gear—can seriously degrade the quality of stock assessments. The volume makes recommendations for means to improve stock assessments and their use in fishery management.
Keywords: Agriculture; Earth Sciences